Reverse or Hemi Shoulder Arthroplasty in Proximal Humerus Fractures: A Single-Blinded Prospective Multicenter Randomized Clinical Trial. Issue 5 (May 2021) - Laas, Niels; Engelsma, Yde; Hagemans, Frans J.A.; Hoelen, Max A.; van Deurzen, Derek F.P.; Burger, Bart J.
Abstract : Objectives: To compare outcomes between hemiarthroplasty (HA) and reversed shoulder arthroplasty (RSA) as a treatment for dislocated 3-part and 4-part proximal humerus fractures in the elderly population. Design: Prospective multicenter randomized controlled trial. Setting: Three Level-1 trauma centers. Patients/Participants: This study included 31 patients of which 14 were randomized into the HA group and 17 into the RSA group. Intervention: Patients randomized to the HA group were treated with a cemented-stem Aequalis-fracture HA and patients randomized to the RSA group with a cemented-stem Aequalis-fracture RSA. Main Outcome Measurements: Primary outcomes consisted of range of motion and constant score. Secondary outcomes were the visual analog scale for pain, DASH score, SF-12 scores, and radiographic outcomes. Results: After 6 and 12 months of follow-up, RSA showed a significant higher anterior elevation (105 degrees vs. 80 degrees, P = 0.002 and 110 degrees vs. 90 degrees, P = 0.02, respectively) and constant score (60 vs. 41, P = 0.01 and 51 vs. 32, P = 0.05, respectively) compared with HA. There were no significant differences in external and internal rotation. Also, visual analog scale pain, DASH scores, SF-12 scores, and radiological healing of the tuberosities and heterotopic ossification did not show any significant differences between groups. Conclusion: RSA showed significant superior functional outcomes for anterior elevation and constant score compared with HA for dislocated 3-part and 4-part proximal humerus fractures after short-term follow-up. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.